Is there anybody in there? Entomological evidence from a boat burial at Øksnes in Vesterålen, northern Norway - Panagiotakopulu, Eva; Buckland, Paul C.; Wickler, Stephen (PLOS ONE, 2018)
Source at https://doi.org/10.1371/journal.pone.0200545 . Although there are several well preserved Viking boat burials from Norway, until recently palaeoecological research on their context has often been limited. Research on fossil insect remains in particular can provide valuable forensic information even in the absence of an actual body. Here we present archaeoentomological information from a boat burial at Øksnes in Vesterålen, northeast Norway, an area where Norse and Sami traditions overlap. Excavated in 1934, organic preservation from the burial was limited to parts of the boat and a clump of bird feathers which were preserved in the Tromsø University Museum, and from which fossil insects were recovered. The insect assemblage from Øksnes includes the blowfly, Protophormia terraenovae (Rob.-Des.), which indicates exposure of the body and the probable timing of the burial. The high numbers of the human flea, Pulex irritans L. from among the feathers, suggests that these, probably from a pillow under the corpse, originated from within a domestic context. Deposition of flowers as part of the burial is discussed on the basis of the insect fauna. The absence of a body and any associated post burial decay fauna implies its exhumation and disposal elsewhere and this is discussed in the context of other exhumed medieval burials and Saga and other sources.